2016
DOI: 10.1097/aog.0000000000001335
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Networks, Medical–Legal Climate, and Patient Advocacy on Surgical Options

Abstract: The dissemination of information online and resultant public discourse through social media and other online channels has influenced the practice of medicine in dramatic ways. Physicians have historically worked to develop new techniques and devices for the benefit of their patients. It is only a more recent phenomenon, however, that these tools are either removed or their use is curtailed largely driven by anecdotal reports; passionate, vocal, often media-savvy advocates; and plaintiff attorneys. The use of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The American College of Obstetricians and Gynecologists published a commentary in 2016 regarding the role of social networks on surgical options and how the use of power morcellation, hysteroscopic tubal sterilization, and mesh in urogynecologic procedures has been impacted by the dissemination and discourse of information on social media. Their message was for healthcare providers to be more involved in the debate so that "public fervor" does not outweigh evidence-based medicine [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American College of Obstetricians and Gynecologists published a commentary in 2016 regarding the role of social networks on surgical options and how the use of power morcellation, hysteroscopic tubal sterilization, and mesh in urogynecologic procedures has been impacted by the dissemination and discourse of information on social media. Their message was for healthcare providers to be more involved in the debate so that "public fervor" does not outweigh evidence-based medicine [8].…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of works include commentaries, perspectives, and editorial pieces [5−7]. The content of these pieces focuses on dissemination of scientific evidence and education with respect to the patient, the practicing physician, or the physician−patient relationship [5,6,8]. Only one published study surveyed the use of social media by patients with or without gynecologic pain and found that those with pain were more likely to use social media to learn about or manage their condition than those without gynecologic pain [5].…”
mentioning
confidence: 99%
“…[13][14] The value of social media in the dissemination of scientific evidence is clearly reflected by the response of the medical community. There has been an increase in the number of social media publications appearing in medical journal articles 15,16 , in the inclusion of social media workshops at national conferences 17 and in the engagement of annual meeting participants (such as #AAGL2015, #ACOG16, #SGS2016). 16 Some centers have started social media training programs for health professionals 18 and, organizations such as the CDC and ACOG have developed social media(SoMe) guidelines.…”
mentioning
confidence: 99%
“…Public outcry can unduly preclude the use of safe alternatives [5]. The pink ribbon campaign for breast cancer screening used public fervor to transform a disease into a market-driven industry, which is deliberately flying in the face of the scientific evidence challenging the clinical benefit of screening [6].…”
mentioning
confidence: 99%